Vascular Stiffness in Aging and Disease - Vatner, Stephen F.; Zhang, Jie; Vyzas, Christina; Mishra, Kalee; Graham, Robert M.; Vatner, Dorothy E. (Frontiers in Physiology, 2021)
The goal of this review is to provide further understanding of increased vascular stiffness with aging, and how it contributes to the adverse effects of major human diseases. Differences in stiffness down the aortic tree are discussed, a topic requiring further research, because most prior work only examined one location in the aorta. It is also important to understand the divergent effects of increased aortic stiffness between males and females, principally due to the protective role of female sex hormones prior to menopause. Another goal is to review human and non-human primate data and contrast them with data in rodents. This is particularly important for understanding sex differences in vascular stiffness with aging as well as the changes in vascular stiffness before and after menopause in females, as this is controversial. This area of research necessitates studies in humans and non-human primates, since rodents do not go through menopause. The most important mechanism studied as a cause of age-related increases in vascular stiffness is an alteration in the vascular extracellular matrix resulting from an increase in collagen and decrease in elastin. However, there are other mechanisms mediating increased vascular stiffness, such as collagen and elastin disarray, calcium deposition, endothelial dysfunction, and the number of vascular smooth muscle cells. Populations with increased longevity, who live in areas called “Blue Zones”, are also discussed as they provide additional insights into mechanisms that protect against age-related increases in vascular stiffness. Such increases in vascular stiffness are important in mediating the adverse effects of major cardiovascular diseases, including atherosclerosis, hypertension and diabetes, but require further research into their mechanisms and treatment.